2001
DOI: 10.1103/physreve.64.066617
|View full text |Cite
|
Sign up to set email alerts
|

Solitary waves in systems with separated Bragg grating and nonlinearity

Abstract: The existence and stability of solitons in a dual-core optical waveguide, in which one core has Kerr nonlinearity while the other one is linear with a Bragg grating written on it, are investigated. The system's spectrum for the frequency omega of linear waves always contains a gap. If the group velocity c in the linear core is zero, it also has two other, upper and lower (in terms of omega) gaps. If c not equal to 0, the upper and lower gaps do not exist in the rigorous sense, as each overlaps with one branch … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(19 citation statements)
references
References 19 publications
2
17
0
Order By: Relevance
“…1 shows the hyperbola L + γ + = 1/2, along which the average Kerr coefficient (9) exactly vanishes. The finite separation between the lower stability boundary and the dashed curve can be measured by the average value γ of the Kerr coefficient (9). The smallest value for γ found on the lower boundary is approximately 0.3.…”
Section: The Stability Diagram For the Gap Solitonsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 shows the hyperbola L + γ + = 1/2, along which the average Kerr coefficient (9) exactly vanishes. The finite separation between the lower stability boundary and the dashed curve can be measured by the average value γ of the Kerr coefficient (9). The smallest value for γ found on the lower boundary is approximately 0.3.…”
Section: The Stability Diagram For the Gap Solitonsmentioning
confidence: 99%
“…It has been demonstrated that a part of the family is stable, and another part is unstable [6,7]. Exact gap-soliton solutions can also be found, and their stability can be investigated, in generalized versions of the model (1), (2), which describe a system of parallelcoupled nonlinear and linear fibers with BG written on both of them [8], including also an especially interesting case when BG is written only on the linear core, so that the nonlinearity and BG are separated [9].…”
Section: Introduction and Formulation Of The Modelmentioning
confidence: 99%
“…To date, solitons with a velocity of 23% of the speed of light in the medium have been experimentally observed [22]. Gap solitons have also been predicted in more sophisticated nonlinear systems such as dual-core fibers equipped with Bragg gratings [23,24], waveguide arrays [25], quadratic nonlinearity [26][27][28], photonic crystals [29][30][31], and cubic-quintic nonlinearity [32,33].…”
Section: Introductionmentioning
confidence: 97%
“…It has theoretically been shown that inhomogeneity within BGs such as local defects and apodization may CONTACT Javid Atai javid.atai@sydney.edu.au also be utilized to generate slow or quiescent solitons (14)(15)(16). BG solitons have also been studied in more sophisticated photonic bandgap materials such as waveguide arrays (17), photonic crystals (18,19), dual-core systems (20)(21)(22)(23)(24)(25)(26) as well as diverse nonlinear media such as quadratic nonlinearity (27,28), sign-changing Kerr nonlinearity (29) and cubic-quintic nonlinearity (30)(31)(32)(33) and more recently matter-wave structures such as Bose-Einstein condensate (34,35). In the case of nonuniform gratings, the standard model of BG solitons must be modified to take into account the effect of nonuniformity.…”
Section: Introductionmentioning
confidence: 98%